Calcium-activated chloride current expression in axotomized sensory neurons: what for? - Boudes, Mathieu; Scamps, Frédérique (Frontiers in Molecular Neuroscience, 2012)
Calcium-activated chloride currents (CaCCs) are activated by an increase in intracellular calcium concentration. Peripheral nerve injury induces the expression of CaCCs in a subset of adult sensory neurons in primary culture including mechano-and proprioceptors, though not nociceptors. Functional screenings of potential candidate genes established that Best1 is a molecular determinant for CaCC expression among axotomized sensory neurons, while Tmem16a accounts for inflammation-induced CaCC expression in nociceptors. In nociceptors, such CaCCs are preferentially activated under receptor-induced calcium mobilization contributing to cell excitability and pain. In axotomized mechano- and proprioceptors, CaCC activation does not promote electrical activity and prevents firing, a finding consistent with electrical silencing for growth competence of adult sensory neurons. In favor of a role in the process of neurite growth, CaCC expression is temporally correlated to neurons displaying a regenerative mode of growth. This perspective focuses on the molecular identity and role of CaCC in axotomized sensory neurons and the future directions to decipher the cellular mechanisms regulating CaCC during neurite (re)growth.